FAKTOR-FAKTOR YANG `MEMPENGARUHI INDEPENDENSI AUDITOR - Novitasari, Ferraria; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of the provision of other services i.e: audit service, the length of the relationship between the audit and its client, the size of public accountant office, the competition among public accountant office to the independency of auditor. The results of this study show that: the provision of the other services other than audit service have negative influence to the independency of the auditor, the length of the relationship between the audit and its client has positive influence to the independency of the auditor, the size of public accountant office has negative influence to the independency of the auditor, the competition amoung public accountant offices client has positive influence to the independency of the auditor.Keywords: the provision of other services other than audit service, the length of the relationship between the audit and its client, the size of public accountant office, the competition amoung public accountant office to the independency of auditor.